Transition-metal-free and facile synthesis of 3-alkynylpyrrole-2, 4-dicarboxylates from methylene isocyanides and propiolaldehyde. (6th September 2021) - Huo, Xiaoli; Chen, Xiaojuan; Yu, Liya; Zhang, Chong; Zeng, Linghui; Zhu, Huajian; Shao, Jiaan; Fu, Liping; Zhang, Jiankang
Abstract : A transition-metal-free, facile and efficient method for the synthesis of 3-alkynylpyrrole-2, 4-dicarboxylates was developed. Abstract : A transition-metal-free, facile and efficient method for the synthesis of 3-alkynylpyrrole-2, 4-dicarboxylates from methylene isocyanides and propiolaldehyde with moderate to good yields has been developed. The direct transformation process and good tolerance of various substituents make it an alternative approach to previous protocols, and potential applications of these investigated compounds are expected with or without post-modifications.